Socio-economic and demographic factors that contribute to the growth of the civil aviation industry - Addepalli, Sri; Pagalday, Gerardo; Salonitis, Konstantinos; Roy, Rajkumar (Elsevier, 2018)
The civil aviation industry has captured the world’s share both in terms of operations and markets. The International Civil Aviation Organisation (ICAO) reported an increase of 6.3 percent in passenger traffic to 3.7billion in 2016 based on recorded departures globally. This paper is an effort to understand the driving force for the civil aviation sector based on demand. As per published reports, the trends show the continued growth in the sector even with the inclusion of production challenges in order to meet global market demand. Though the sector is heavily reliant on a variety of challenges and factors, the industry has established itself as the most advanced and lucrative industry that continues to ‘PULL’ the associated industries. This paper identifies and establishes the ‘push’ and ‘pull’ factors under social, demographic and economic factors and how they exercise significant control making the ever-growing industry RESILIENT to changing geo-economic and political landscapes.
Keywords: Manufacturing network; Economics; Logistics